To simplify the expression \(\left(\dfrac{a^{-3}}{b^{2}}\right)^{4}\), we can use the property of exponents \((\frac{x}{y})^n = \frac{x^n}{y^n}\).
-
Start by applying the exponent to both the numerator and the denominator: \[ \left(\dfrac{a^{-3}}{b^{2}}\right)^{4} = \dfrac{(a^{-3})^{4}}{(b^{2})^{4}} \]
-
Now calculate the exponents: \[ (a^{-3})^{4} = a^{-12} \] \[ (b^{2})^{4} = b^{8} \]
-
Substitute these back into the fraction: \[ \dfrac{(a^{-3})^{4}}{(b^{2})^{4}} = \dfrac{a^{-12}}{b^{8}} \]
-
Since \(a^{-12} = \frac{1}{a^{12}}\), we can rewrite this as: \[ \dfrac{a^{-12}}{b^{8}} = \dfrac{1}{a^{12} \cdot b^{8}} \]
So the equivalent expression is: \[ \dfrac{1}{a^{12} \cdot b^{8}} \]
The correct choice is: (Choice B) \(\dfrac{1}{a^{12}\cdot b^{8}}\)